The response of local maize prices to the 1983 currency devaluation in Ghana - Badiane, Ousmane; Shively, Gerald E. (International Food Policy Research Institute, 1997)
This paper investigates the respective roles of spatial integration and arbitrage costs in explaining the adjustment of local prices to policy changes using the example of Ghana. We introduce a model of price formation and market integration that incorporates the price transmission process between local and central markets and also captures the implications for volatility of local prices. We explore the implications of the model for the time-path of price adjustments, as determined directly and indirectly through the marketing sector. We show that the price-adjustment process in a local market is determined by the degree of interdependence between that market and the central market in which a price-shock originates, and estimate the intertemporal and interspatial dynamics of the price adjustment process. Using data from wholesale maize markets in Ghana we find that reductions in local prices and local price variance following the introduction of economic reforms in 1983 can be traced to both local and central market forces, but that differences in the degree of market integration have important implications for long-run changes in arbitrage costs and the evolution of prices in outlying markets.